Improving Urban Public Bus Service Quality: A Review of the Performance Benchmarking - Syazwan Baharum; Suria Haron (International Journal of Supply Chain Management, 2020)
Malaysian nowadays prefer more on private transport such as car and motorcycle compared to public bus. This decision may be due to personal experience when the services do not meet the expected satisfaction. Understanding the key factors of bus performance is important because it related users’ loyalty and ridership issue. However, current practice in Malaysia does not focus on developing and implementing an urban transport benchmarking. The authorities and the operators need to take a transparent action with an intense understanding of user needs in order to enhance the public bus service for foreseeable future. This article reviews an approach that acknowledged by previous studies in an interest of assisting public bus transportation planning that advantage of sustainable public transportation system.